The strategy for the development of depressed areas of the architectural and historical environment of the city of Odessa on the example of Devolanivskyi descent street (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2025)
The article is devoted to the definition of the strategy for the development of depressed areas of the architectural and historical environment of the city center of Odesa. The concept of the strategy for the development of depressed areas is defined, the factors that influence the development of the historic center of the city are identified, and approaches to the renovation of depressed areas in world practice are analyzed.Emphasis is placed on the problem of preservation and continuity of the development of the architectural and historical environment, as well as the new use of objects. The basis for developing the provisions of the strategy for the development of Devolanovskyi Descent in Odesa is the legislative and regulatory framework for the inspection of buildings and structures, the Law of Ukraine “On Regulation of Urban Development”, the 18th extraordinary session of the World Heritage Committee. The inclusion of the historic center of Odesa in the UNESCO World Heritage List, the Law of Ukraine “On Protection of Cultural Heritage”, state design standards, scientific works of leading theorists and practitioners in the field of design in the architectural and historical environment – Arnheim R., Day K., Lynch K., etc. The authors propose approaches to research and design in the architectural and historical environment, peculiarities of the formation of qualitative characteristics (potential) and direction. On the example of student works, the directions and principles pf organization of modern cultural and public complexes based on the historically formed environment are established. The basic concepts, specific of research and design in the architectural and historical environment are clarified. The forms of existence and mechanisms of formation of historical and cultural tradition, concepts of design solutions, continuity of development of a fragment of the architectural and historical environment are determined.
Keywords: depressed territories of the city center; renovation; architectural and historical environment; strategy of development of the historic center; factors influencing the development of the architectural and historical environment; directions of development of the historic center environment; principles of development of the historic environment; priority programs and approaches; indicators of implementation of the strategy if development of the historic environment